Місце та роль педагогічної практики у підготовці майбутніх учителів іноземних мов в Україні та Англії - Бевз, Олена (Studies in Comparative Education, 2015)
У статті досліджено роль педагогічної практики у підготовці майбутніх учителів іноземних мов та визначено можливі шляхи здобуття вчительської професії в Україні та Англії. Виокремлено види педагогічних практик у системі професійно-педагогічної підготовки майбутніх учителів іноземних мов в обох країнах. Визначено нормативно-правову базу організації та проведення педагогічних практик майбутніх учителів іноземних мов та виділено основні спільні та відмінні риси педагогічних практик в Україні та Англії. В статье рассмотрен вопрос практической подготовки будущих учителей иностранных языков в высших учебных заведениях Украины и Англии. Определены возможные варианты соискания профессии учителя. Обозначены виды педагогической практики в системе профессионально-педагогической подготовки будущих учителей иностранного языка в обеих странах. Рассматривается законодательная база организации и проведения педагогических практик будущих учителей и анализируются основные общие и отличительные характеристики их практической подготовки. The article deals with the issue of practical training of future foreign language teachers in Ukraine and England. Possible ways of becoming a teacher in both countries are analyzed. The types of teaching practice in the system of professional and educational training are stated. The laws and regulations for organizing and conducting of teaching practice of prospective foreign language teachers in Ukraine and in England are outlined. Special attention is given to the joint project “New Generation School Teacher” initiated by Ministry of Education and Science of Ukraine and British Council Ukraine with the aim to improve the quality of Ukrainian teachers of English pre-service training. Presently key components of pre-service education and training for EFL teachers in Ukraine include: Language strand, Linguistic strand, Psychological and pedagogical strand, ELT Methodology. Teaching practice for students is regarded as a compulsory component of the educational process. It provides the combination of trainee teachers’ theoretical education and practical vocational experience at schools, contributes to developing their creative attitude towards teaching, evaluates their professional standard and determines the level of professional motivation. It offers students the possibility to teach independently and demonstrate their creativeness, stimulates relationships between teaching, research, vocational training and self-education. Students undertake practice after completing theoretical courses in psychology, educational science, foreign language teaching methodology at a comprehensive school. The establishing of partnership between higher educational establishments and schools for practical training of teachers as well as the existing practice of the introduction as a newly-qualified teacher at English schools are considered to be the most noticeable differences in teaching practice in Ukraine and in England.